Preliminary evaluation of anti-termitic activity of Prosopis juliflora leaf extract against Macrotermes spp (Isoptera: Termitidae) - Terefe Tafese Bezuneh (Cogent Environmental Science, 2019)
Considering the harmful effects of the synthetic termiticides and resistance development in the pest population, there is a need to search for economically viable, environmentally-friendly and effective termiticides. Therefore, the screening of alternative antitermiticidal activity from plant based products could be employed as a means in the termite control strategies. The present study was carried out to evaluate the anti-termitic activity of the hexane leaf extract of Prosopis juliflora against the termites of Macrotermes spp. at concentrations of 25, 50, 75 and 100 mg/L. It was found that, the LC50-LC90 values were 33.3–213.98, 12.71–66.33 and 9.41–34.71 mg/L after 24, 48 and 72 h of exposure, respectively. The phytochemical study of the crude extract showed the presence of steroids, saponins, terpenoids, alkaloids and flavonoids which might be responsible for its biocidal activity. These results suggested that hexane leaf extract of P. juliflora possessed biocidal activity aginst termites.